Wolf Moon Blood Moon : Poems - Falco, Edward (Book collections on Project MUSE., 2017)
Ed Falco considers love and the loss of love, what we have today and what we remember of yesterday, the promise of youth and the disappointments and pleasures of aging. By turns whimsical, meditative, and poignant, these poems examine the joys and sorrows of living.